PENGARUH ON STREET PARKING TERHADAP KINERJA RUAS JALAN MOCH. HATTA KOTA KUPANG (Studi Kasus Di Depan RSUD Prof. Dr. W.Z. Johannes) (Eternitas: Jurnal Teknik Sipil, 2025)
On-street parking can affect the performance of the road section due to the reduction in the effective width of the road. This problem occurs on Jl. Moch. Hatta in front of Dr. Prof. W.Z. Johannes Hospital. The purpose of this study was to determine the characteristics of parking on the roadside and its impact on the performance of the road section. The research method uses parking characteristic calculations such as volume, accumulation, duration, index and turnover, while the calculation of road section performance uses the PKJI 2023 method. The results of the study related to the characteristics of on-street parking obtained a parking volume on the left side of the roadside of 261 vehicles and on the right side of 248 vehicles. The highest parking index per hour on the left side of the road for motorcycles was 63% and for cars 96%, while on the right side of the road for motorcycles it was 25% and for cars 90%. These results show that the parking index is dominated by passenger car. The results of the road section performance obtained the highest traffic volume is 1,112 pcu/hour, the capacity in existing conditions is 1,776 pcu/hour with a DJ value of 0.63 (LOS C). The average speed obtained is 16.06 km/hour and the free flow speed obtained is 42.854 km/hour. The level of road service from the relationship between speed and DJ is obtained as LOS E. The effect of on-street parking on the performance of the road section is 42% to 68%. This is calculated based on two simulation condition, first condition if there only 1 sided on-street parking and the second condition if on-street parking is eliminated.
Keywords: On-street Parking; Performance; Road Section